‘Are Mindfulness Techniques Practised in the Early Years Setting?’: A Study of the Use of Mindfulness in the Early Years - Palmer, Edel (TARA, 2021)
This research aimed to gain insight into early years educators’ understanding of mindfulness and its; effects, as well as their perceptions regarding its practice with young children.
Are Mindfulness Techniques Practised in the Early Years Setting?
Journal article
Keywords: Early Childhood Education; Mindfulness; Mindfulness Effects and Benefits; Mindfulness (Psychology)